Analysis Of Earning Pershare (Eps) As Moderating Variable The Effect Of Return On Assets (Roa) On Stock Prices In Non Lq 45 Cement Sub-Sector Companies Listed On The Stock Exchange For The 2014-2019 Period - Kartika Sari; Putri Eriska Indriani (Cita Konsultindo Research Center, 2022)
An investor's decision to buy a stock is influenced by fundamental analysis of financial statements and technical analysis of stock price movements. It is undeniable that stock prices are set in the capital market in accordance with the demand and supply that occurs. The selection of shares purchased cannot be separated from the amount of profit desired by investors. This study aims to determine whether Earning Per Share (EPS) moderates the effect of Return On Assets (ROA) on stock prices in non-LQ45 Cement Sub-Sector Companies listed on the IDX for the 2014-2019 period. The purposive sampling method was chosen to determine the sample in this study with the criteria that the company is not included in LQ45 and publishes financial statements in the period in question. The data analysis technique used in this research is descriptive statistics and the Moderated Regression Analysis (MRA) test. The results of this study indicate that the Return on Assets (ROA ) has an effect on stock prices, however, Earning Per Share ( EPS ) does not moderate the effect of Return On Assets (ROA) on stock prices in non-LQ45 cement sector companies. Keywords: Earning Per Share, Stock Price, and Return on Asset Ratio